2020
DOI: 10.21203/rs.3.rs-15802/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships between abnormal neural activities and cognitive impairments in patients with drug-naive first-episode schizophrenia

Abstract: Background Prior resting state functional magnetic resonance imaging studies via the regional homogeneity (ReHo) method have demonstrated inconsistent and conflicting results because of several confounding factors, such as small sample size, medicinal influence, and illness duration. Relationships between ReHo measures and cognitive impairments in patients with drug-naive first-episode schizophrenia (dn-FES) are rarely reported. This study was conducted to explore the correlations between ReHo measures, cognit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…They are commonly used to identify the local neural activity abnormalities in patients with schizophrenia and are considered to be a reliable imaging marker, but the results may be influenced by medication and duration of illness, thus leading to inconsistent results. 8,[10][11][12][13] For instance, current cross-sectional studies found increased ALFF/fALFF and ReHo in putamen in first-episode schizophrenia, 14,15 while others failed to replicate the above results in chronic patients. 16,17 To the best of our knowledge, a simultaneous meta-analysis of the two measures of spontaneous brain activity based on resting-state fMRI has not been performed.…”
Section: Review Articlecontrasting
confidence: 56%
See 3 more Smart Citations
“…They are commonly used to identify the local neural activity abnormalities in patients with schizophrenia and are considered to be a reliable imaging marker, but the results may be influenced by medication and duration of illness, thus leading to inconsistent results. 8,[10][11][12][13] For instance, current cross-sectional studies found increased ALFF/fALFF and ReHo in putamen in first-episode schizophrenia, 14,15 while others failed to replicate the above results in chronic patients. 16,17 To the best of our knowledge, a simultaneous meta-analysis of the two measures of spontaneous brain activity based on resting-state fMRI has not been performed.…”
Section: Review Articlecontrasting
confidence: 56%
“…Then, after a detailed review of the full texts, 18 datasets of rs-fMRI studies, 1,039 Dn-FES patients, and 1,425 HCs were included in our meta-analysis. 8,10,14,15,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] The sample characteristics and imaging information of the included studies are shown in Table 1 and Figure 1.…”
Section: Search Results and Sample Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig. 1, our search strategy initially identified 1816 studies, of which 18 studies were eligible for meta-analysis including a total of 652 patients with schizophrenia and 596 healthy controls [10][11][12][13][14][15][24][25][26][27][46][47][48][49][50][51][52][53] . Among these studies, three studies were longitudinal designs, and we only included the results of between-group comparison using baseline data 13,46,51 .…”
Section: Included Studiesmentioning
confidence: 99%